If the curve y = A . e x + B . e 2 x + C . e 3 x satisfies the differential equation a . d x 3 d 3 y + b . d x 2 d 2 y + c . d x d y + d . y = 0
Find the value of a × d b × c
Check out more questions on differential equations
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
What a solution sir !!! Hats off to you. Great.
i think you need to say something about the curve Y=0 . (for a=0,b=0,c=0,d=0)
y = a e x + b e 2 x + c e 3 x
d x d y = a e x + 2 b e 2 x + 3 c e 3 x
d x 2 d 2 y = a e x + 4 b e 2 x + 9 c e 3 x
d x 3 d 3 y = a e x + 8 b e 2 x + 2 7 c e 3 x
Substituting in given equation,
a d x d y + b d x 2 d 2 y + c d x d y + d y = 0
⇒ a ( a + b + c + d ) e x + b ( 8 a + 4 b + 2 c + d ) e 2 x + c ( 2 7 a + 9 b + 3 c + d ) e 3 x = 0
Since e x , e 2 x and e 3 x cannot be 0 or negative, their coefficients must be 0.
a + b + c + d = 0 ..... ( 1 )
8 a + 4 b + 2 c + d = 0 ..... ( 2 )
2 7 a + 9 b + 3 c + d = 0 ..... ( 3 )
( 2 ) − ( 1 ) 7 a + 3 b + c = 0 ..... ( 4 )
( 3 ) − ( 2 ) 1 9 a + 5 b + c = 0 ..... ( 5 )
( 5 ) − ( 4 ) 1 2 a + 2 b = 0 ..... ( 6 )
Let a = 1 . It gives b = − 6 , c = 1 1 , d = − 6
Hence a × d b × c = 1 1
There is no need to substitute a=1. You may get all other variables in terms of a. While calculating fraction, a would cancel out.
Exactly !! I did the same way ! btw Nice Solution ! :)
we know from superposition that each of
e
x
e
2
x
and
e
3
x
are solutions to the differential equation. Hence, 1,2 and 3{powers of solutions} are solutions to the characteristic eq. of the differential equation
which is..............
a
r
3
+ b
r
2
+ cr + d = 0
(
cubic equation
)
we already know the roots
(1,2, and 3)
and by using vietas' formulas we find the answer to be of the form .....
b × c / a × d = [{sum of roots} x {sum taken two at a time}]/{product of roots} which when computed gives 11 as the answer.
That's exactly how I did it
i sued determinants without wasting time finding a,b,c,d separately but a c/b d directly
Done exactly the same as Sandeep
y = a e x + b e 2 x + c e 3 x . . . . . . . ( 1 )
y ′ = a e x + 2 b e 2 x + 3 c e 3 x = ( a e x + b e 2 x + c e 3 x ) + b e 2 x + 2 c e 3 x
Using ( 1 )
y ′ = y + b e 2 x + 2 c e 3 x = y + ( y − a e x ) + c e 3 x
y ′ = 2 y + c e 3 x − a e x . . . . . . . . . ( 2 )
y ′ ′ = 2 y ′ + 3 c e 3 x − a e x = 2 y ′ + ( c e 3 x − a e x ) + 2 c e 3 x
Using ( 2 )
y ′ ′ = 2 y ′ + ( y ′ − 2 y ) + 2 c e 3 x
y ′ ′ = 3 y ′ − 2 y + 2 c e 3 x . . . . . . . . . . ( 3 )
Using ( 3 )
⇒ y ′ ′ ′ = 3 y ′ ′ − 2 y ′ + 6 c e 3 x = 3 y ′ ′ − 2 y ′ + 3 ( 2 c e 3 x )
y ′ ′ ′ − 3 y ′ ′ + 2 y ′ = 3 ( y ′ ′ − 3 y ′ + 2 y ) = 3 y ′ ′ − 9 y ′ + 6 y
y ′ ′ ′ − 6 y ′ ′ + 1 1 y ′ − 6 y = 0
a × d b × c = 1 1
Problem Loading...
Note Loading...
Set Loading...
Given Primitive : y = a e x + b e 2 x + c e 3 x
⟹ y . e − x = a + b e x + c e 2 x
Differentiating wrt x
e − x ( d x d y − y ) = b e x + 2 c e 2 x
⟹ e − 2 x ( d x d y − y ) = b + 2 c e x
Differentiating wrt x again
e − 2 x ( d x 2 d 2 y − 3 . d x d y + 2 y ) = 2 c e x
⟹ e − 3 x ( d x 2 d 2 y − 3 . d x d y + 2 y ) = 2 c
Differentiating wrt x again, we have
e − 3 x ( d x 3 d 3 y − 6 . d x 2 d 2 y + 1 1 . d x d y − 6 y ) = 0
As e − 3 x = 0
Therefore Required differential equation is
d x 3 d 3 y − 6 . d x 2 d 2 y + 1 1 . d x d y − 6 y = 0
On comparing coefficients we get a × d b × c = 1 1 .